Phenolic compounds in wine and their antioxidative effects on diseases prevention (Revista de Ciências Agroveterinárias, 2009)
Phenolic compounds are widely spread in vegetable kingdom. Among fruits, grape (Vitis vinifera L.) is one of the most important source of phenolic compounds, like flavonoids (anthocyanidins and flavonones), stilbene (resveratrol), phenic acid (derived from cinnamic and benzoic acids) and a large variety of tannins. In the last decades, great attention has been directed to the free radicals participation in the pathogenesis of several non-transmissible diseases. Studies have proved the antioxidant properties of phenolic compounds in products made by grapes, especially red wine. Another wine compound is ethanol, which reinforces cardiovascular protection. This study had the objective of investigating the biological properties of phenolic compounds in wine, looking for their composition, chemical structure and antioxidant activity. It is equally important to keep in mind that wine can benefit health by moderate drinking. According to several researchers, a proper diet and the moderate wine consumption (300 mL/day) are adequate strategies to protect and enhance health through several physiological mechanisms.
Keywords: wine; phenolic compounds; antioxidants.